Intelligent Framework of Rural Tourism Marketing Big Data Mining based on PHP Algorithm of Intelligent Ledger System - Fan, Huanhuan (2022 International Conference on Edge Computing and Applications (ICECAA), 2022)
Design and develop a ledger system based on the front-end and back-end separation architecture. The system adopts the design concept of mobile first, and deeply customizes the functions and user interface for smart phones. Based on this, this paper briefly introduces the definition of rural ecotourism, analyzes the current situation of rural ecotourism marketing in my country, and proposes the precision of rural ecotourism in the big data environment. Marketing strategy to help the development of rural ecotourism in my country. The regional differences and dispersion of WeChat marketing performance are large, and the online customer relationship is dominated by positive emotions. It aims to create social and economic value from rural social big data, implement big data-driven precision marketing innovation strategies, enhance the competitiveness of rural digital economy, and promote rural smart growth and regional coordination and sustainable development.